Infestation of Helicoverpa armigera (Hubner) and Ostrinia furnacalis Guenee on three tropical altitude variations - Ginting, Sempurna; Chozin, Mohammad; Sudjatmiko, Sigit (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2023)
Pest infestation is a major problem in corn cultivation because it causes a decrease in crop productivity or even crop failure. This study aimed to evaluate the level of crop damage caused by Helicoverpa armigera and Ostrinia furnacalis in three tropical altitude variations. Ten hybrid corns from cross-breeding strains and three commercial hybrid corn varieties were evaluated at three locations with different altitudes, classified as lowland (30 masl), midland (600 masl), and highland (1000 masl). The evaluation was carried out on the level of crop damage and plant resistance. The results showed that the highest percentage of H. armigera attack on hybrid corn was 75% at Caps 17B x Caps 23 (moderately susceptible) at the lowland and the lowest was 8% at Caps 2 x Caps 17A (resistant). The percentage of H. armigera attack was 100% at Caps 15 x Caps 22 (very susceptible) and the lowest was the evaluation of Caps 5 x Caps 17B was 58% (susceptible) at the midland. Meanwhile, the highest attack percentage was 92% on the Caps 17A x Caps 17B, Caps 17A x Caps 22, and Caps 5 x Caps 22 hybrids (very susceptible), while the lowest was 67% on the Caps 3 x Caps 17B and Secada hybrids (moderately susceptible) at the highland. O. furnacalis attack showed that all hybrid corns were classified as resistant except for Caps 5 x Caps 22 and Paragon was moderately resistant with a percentage attack of 25% at lowland. At the midland, Caps 5 x Caps 17B hybrid corn was classified as very susceptible with an attack of 92%, while Caps 15 x Caps 22 was classified as resistant with an attack percentage of 8%. At an altitude of 1000 masl, Caps 17A x Caps 17B, Caps 3 x Caps 17A, and Caps 5 x Caps 17B were moderately resistant with an attack percentage of 33% and other hybrids were resistant with an attack percentage of 8%.